P014 An audit of bone health assessment in patients admitted to hospital with a fracture following a fall. (26th April 2021) - Kimpton, James; Wong, Barnaby; Amarnani, Raj; Loader, Martin; Fong, Christopher; Mannan, Imran
Abstract: Background/Aims   Over three million people in the UK have osteoporosis; and are at a substantially increased risk of fragility fractures. There are approximately 536, 000 new fragility fractures each year in the UK, with substantial associated morbidity and health service burden. Preventing fragility fractures is thus clinically and economically important and will result in substantial savings for health and social care. The aim of this audit was to assess and improve falls and bone health assessments in a high-risk patient group at a central London hospital. Methods   Data was collected over a 2-month period (02/05/2019-28/06/2019) of consecutive patients over the age of 50 admitted to hospital following a fall and fracture. We used the 2017 National Osteoporosis Guidelines Group, NICE clinical guideline on falls in older people (CG161) and the local hospital osteoporosis screening policy as the audit standards. Patient notes were reviewed to assess for evidence of bone health assessment and key falls assessment domains having taken place. Results   43 patients were included; 8 of which had a neck of femur fracture (NOF). Table 1 demonstrates the different components that we included in the falls assessment. Only 5 (12%) of all of the patients had a full falls assessment recorded. In all domains, patients with a NOF were more likely to have a more complete falls assessment than patients with other fractures, especially fundamental components such as osteoporosis risk assessment. Conclusion   Key aspects of falls and bone health assessment are simple and quick to do, yet often not done in patients admitted with a fracture following a fall. These measures are highly valuable in the long term to mitigate future fragility fracture risk. Our results show that post fall assessment, including bone health, are performed more often in patients with NOF than non-NOF fractures. There is large scope for improvement in practice for this at-risk cohort of patients. Therefore, going forward, our next steps are to create an education programme and embed a standardised, simple proforma into electronic healthcare records to guide post fall bone health assessment. Disclosure   J. Kimpton: None. B. Wong: None. R. Amarnani: None. M. Loader: None. C. Fong: None. I. Mannan: None.